The economy of Deuteronomy's core - Guillaume, Philippe (Worlds of the ancient Near East and Mediterranean, 2022)
"Grounded in the text itself, The Economy of Deuteronomy's Core reads Deuteronomy 12-26 in light of what we know about Ancient Near Eastern economies. The results open new horizons regarding the origins of the Deuteronomic laws"--